The effect of body mass index on the outcome of pregnancy in women with recurrent miscarriage - Winnie Lo; Raj Rai; Aisha Hameed; Susan R Brailsford; Ahlam A Al-Ghamdi; Lesley Regan (Journal of Family and Community Medicine, 2012)
Background: Maternal obesity is associated with menstrual disorders, infertility and sporadic miscarriages. Recurrent miscarriage (RM) affects at least 1% of couples trying to conceive. In over 50% of cases, the cause of the loss of pregnancy remains unexplained. The aim of this study was to determine the relationship between maternal Body Mass Index (BMI) and future outcomes of pregnancy in couples with "unexplained" RM. Methods and Results: All couples referred to the specialist recurrent miscarriage clinic at St. Mary′s Hospital, London, were investigated for an underlying cause. Those with unexplained RM were eligible. Demographic and clinical data were retrieved from a computerised database and medical records. The World Health Organisation (WHO) classification of BMI was used. Univariate analysis demonstrated that BMI, maternal age, number of previous miscarriages and ethnicity were significantly associated with pregnancy outcome. Logistic regression demonstrated that maternal obesity (BMI ≥ 30 kg/m 2 ) significantly increased the risk of miscarriage in couples with unexplained RM (OR 1.73; 95% CI 1.06 - 2.83). Asian women with a BMI similar to Caucasian women had a higher risk of a further miscarriage (OR 2.87, 95% CI, 1.52 - 5.39). Conclusions: Maternal obesity is an independent factor associated with an increased risk of miscarriage in couples with RM. All women with RM should have their BMI recorded at their first clinic visit. The potential effect of weight loss on the outcome of subsequent pregnancies should be assessed in future studies. The increased risk of miscarriage in Asian women needs to be explored further.